The Growing Up in Australia study content: What are we asking, who are we asking and why? - Millward, C (My University, 2003)
This paper describes the content of the Growing up in Australia study, which aims to consider the influence of social, familial, parental and child characteristics, dynamics and relationships in order to predict their effects on child outcomes and to suggest policy strategies and interventions. The author discusses the study domains and design teams, strengths of the design, instruments used, and processes.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology